Choroba nowotworowa – w obliczu zagrożenia życia - Paul-Kańska, Joanna (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
The article presents a multi – dimensional look at the issue of coping with stress, situating health monitoring and the sense of self – effectiveness in people with recognized cancer. The results of self – studies were displayed, showing whether and to what degree the strategies of managing the disease depend on the subjects’ sex. The existence of the relationship between the tested variables (situating health monitoring and the sense of self – effectiveness) and the strategies of coping with the disease stress, was proved.